2008
DOI: 10.1016/j.catcom.2007.05.045
|View full text |Cite
|
Sign up to set email alerts
|

Promoting effect of Pt addition to Ni/CeO2/Al2O3 catalyst for steam gasification of biomass

Abstract: The modification of Ni/CeO 2 /Al 2 O 3 with Pt can make the activation by H 2 reduction unnecessary, and this indicates that the Pt/Ni/CeO 2 /Al 2 O 3 catalyst can be activated automatically by the compounds contained in tar. This can be explained by the enhancement of the Ni reducibility by the addition of Pt. The results of the temperature programmed reduction with H 2 also support this enhancement. Furthermore, the addition of 0.1% Pt to Ni/CeO 2 /Al 2 O 3 (4wt% Ni, 30wt% CeO 2) enhanced the performance in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(38 citation statements)
references
References 35 publications
2
35
1
Order By: Relevance
“…This indicates that the intermetallic compounds are not formed, but Pt-Ni alloy phase is formed. This behavior is supported by previous reports [9,[31][32][33]. The coordination number of the Pt-Ni bond was much larger than that of the Pt-Pt bond on Pt(C, 0.4)+Ni(N, 10.6).…”
Section: Catalyst Characterizationsupporting
confidence: 79%
“…This indicates that the intermetallic compounds are not formed, but Pt-Ni alloy phase is formed. This behavior is supported by previous reports [9,[31][32][33]. The coordination number of the Pt-Ni bond was much larger than that of the Pt-Pt bond on Pt(C, 0.4)+Ni(N, 10.6).…”
Section: Catalyst Characterizationsupporting
confidence: 79%
“…[21][22][23] A number of catalysts have been proven to be active for hydrogen production and are stable towards deactivation in biomass gasification/reforming, which are mainly the platinum group metals (e.g. Ph, Rt, Pd, Ru) based catalysts [23][24][25][26][27]. However, the high cost of noble metal-based catalysts discourages the practical application of biomass gasification/ pyrolysis-reforming.…”
Section: Introductionmentioning
confidence: 99%
“…Corujo et al 52 reported a more than 5 wt.% amount of coke formation on a Ni/dolomite catalyst for steam gasification of forestry residue. In addition a higher amount (>10wt.%) of coke formation was reported for gasification of biomass using a Ni/Al2O3 catalyst 53 .…”
Section: Gas Concentrationmentioning
confidence: 99%
“…Among them, Al2O3 is regarded as an effective support, in particular, in relation to the catalytic activity for hydrogen production and thermal stability 17,18 . The introduction of CeO2 to Ni-catalysts has been reported to enhance the catalytic performance, and the formation of the Ni-CeO2 nanocomposite was responsible for the better catalytic performance in terms of the prohibition of catalyst sintering and coke formation on the surface of the reacted catalysts 12,[18][19][20] 28 .…”
Section: Introductionmentioning
confidence: 99%